SARS-CoV-2 pandemia in Lombardy: the impact on family Paediatricians - Rinaldo Missaglia; Michael Belingheri; Laura Antolini; Monica de' Angelis; Luca Brivio; Michele Augusto Riva; Simonetta Genovesi (BMC, 2020)
Abstract As health care workers (HCWs) who care for children, who usually demonstrate milder symptoms than adults, family paediatricians have an increased risk of exposure to coronavirus. In April 2020, the Sindacato Medici Pediatri di Famiglia (SIMPeF), provided its members with rapid tests to detect antibodies against SARS-CoV-2; 1240 individuals, including 377 paediatricians, 108 staff members of pediatric clinics, and 755 cohabitant relatives of paediatricians, were tested in Lombardy, the most affected Italian region. The global prevalence of IgG antibodies in these individuals was 20.7%, which is higher than that of the general population and other HCWs. More than 70% of subjects with IgG antibodies presented symptoms, and 4.9% needed hospitalization. In addition, 64.2% of the study participants reported close contacts with a suspected case of COVID-19, while 72.9% of the family paediatricians reported occupational exposure to the disease. The initiative of the SIMPeF has been useful in assessing the impact of the COVID-19 pandemic on paediatric settings, as well as in raising paediatricians' awareness of the spreading of coronavirus.